A Casein Kinase II Phosphorylation Site in AtYY1 Affects Its Activity, Stability, and Function in the ABA Response - Wu, Xiu-Yun; Li, Tian (Frontiers in Plant Science, 2017)
The phosphorylation and dephosphorylation of proteins are crucial in the regulation of protein activity and stability in various signaling pathways. In this study, we identified an ABA repressor, Arabidopsis Ying Yang 1 (AtYY1) as a potential target of casein kinase II (CKII). AtYY1 physically interacts with two regulatory subunits of CKII, CKB3 and CKB4. Moreover, AtYY1 can be phosphorylated by CKII in vitro, and the S284 site is the major CKII phosphorylation site. Further analyses indicated that S284 phosphorylation can enhance the transcriptional activity and protein stability of AtYY1 and hence strengthen the effect of AtYY1 as a negative regulator in the ABA response. Our study provides novel insights into the regulatory mechanism of AtYY1 mediated by CKII phosphorylation.